To Compare the Effectiveness of Biodentine versus Mineral Trioxide aggregate as Direct Pulp Capping agent in carious exposed permanent tooth - Mahrukh Anwar, Muhammed Bader Munir, Nighat Shafi, Sadia Javed, Maryum Virda, Sana Akram (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the effectiveness of Biodentine versus mineral trioxide aggregate as direct pulp capping agent in carious exposed permanent tooth Study Design: Randomized controlled trial Placeand duration: Operative Dentistry, Department of de’Montmorency College of Dentistry / Punjab Dental Hospital, Lahore From 29-07-16 to 30-01-17 Methods: Sample size of 75 in each group (using non-probability) calculated using 80 percent power, 5% level of significance with expected percentage of effectiveness (lack of periapical radiolucency) among groups i.e. 92.68%19 in Biodentine group vs. 78%20 in mineral trioxide group aggregate as direct pulp capping agent. Data was entered and analyzed with IBM SPSS 20. Level of significance was kept at p-value ≤ 0.05. Results: Total 150 patients, 82 are male and 68 are female. The age of patients was 18-45 years. The Mean and SD of age of patients is 30±7.916. In group I, 57(75%) showed efficacy and 18(25%) showed failure of efficacy while in group II 72 (95%) showed efficacy and 3 (5%) showed failure of efficacy after 3 months. Comparison of efficacy shows that group II Biodentinehas better efficacy as compared to group I. Conclusion: It is concluded that Biodentine is more effective than MTA.It can be used as bulk fill, simplify the pulp capping procedure. Keywords: direct pulp capping, vital pulp therapy, efficacy of newer pulp capping materials, MTA and Biodentine.